Motives of using fine arts students to social networking sites in the dissemination of awareness of theatrical knowledge (Journal of the College of Basic Education, 2020)
The research deals with an important topic of digital technology for the theatrical arts, which contributes to the expansion and development of (artistic and scientific knowledge awareness for students of theatrical arts), through social networking sites, to the development of electronic digital technologies that have occurred in their multiple sites, and easy access to and research on digital technical knowledge (artistic and scientific In the field of arts, after the wide and large openness to the communication sites (Arab and international) and its various specialties of human and scientific, especially in the field of (arts and entertainment) as a means of communication media for the visual and audio arts, for product The theatrical and cinematic performances that encouraged the increase of followers and viewers, especially students of the performing arts in particular, because there are many followers to find out the latest methods and theories (acting - directing - criticism - techniques) for academic theatrical performances.Therefore, this research tries to find out (the motives of using the technical and scientific knowledge awareness of theatrical arts students, through the students' answers to the questionnaire , questionnaires prepared for this purpose, which contributes to adding knowledge and technical awareness to practice the artistic profession, in the field of festivals and conferences to produce theatrical performances, As well as the psychological specificity of the aspirations and aspirations of these students, which tend to love knowledge and exploration of the use of modern digital technologies and practice.The importance of this research is motivated by the follow-up of contemporary social media sites, to thwart the processes of influencing and influencing the aspirations and desires of students, in determining their attitudes towards the various artistic and scientific theatrical performances (local - Arab - international), with the technical competence in the production of theatrical performances (tragic - comedy). After researching and investigating multiple websites, which contribute significantly to increasing (knowledge, scientific and technical and technical awareness), to draw their own perception in the development of theatrical theories and modern technical schools, And the production of research and studies in the light of the data, information and ideas, in increasing access to (motivations of awareness of technical knowledge of theatrical).Although the faculties of the performing arts provide some social networking sites, within their practical laboratories that embody the developments (technical - artistic - scientific) in the field of theatrical performances, which contribute to increasing the availability of (scientific knowledge of artistic science) modern.Digital technological development has created new sites for social media, which have surpassed the barriers (time and place) in daily and group chat dialogues, on Facebook, YouTube, Twitter and various other modern websites, which revealed many talents for itsfollowers in the field of preparing and presenting programs.A critical visual comic, highlighting the talents of acting, directing, and diction in adopting the appropriate vocal class to imitate the intended personality, to embody its natural dimensions, which include features of contentment and influence among its recipients and followers, which contribute to the creation of relationships (social - Cultural - artistic - educational), based on human cognitive motives carrying common scientific and artistic awareness.These discussions, dialogues and chats on social networking sites, screened a lot of scientific, technical and technical knowledge that is not without positive benefits and tragic negative.